2020
DOI: 10.1089/ars.2019.7763
|View full text |Cite
|
Sign up to set email alerts
|

Central and Peripheral Metabolic Defects Contribute to the Pathogenesis of Alzheimer's Disease: Targeting Mitochondria for Diagnosis and Prevention

Abstract: Significance: Epidemiological studies indicate that metabolic disorders are associated with an increased risk for Alzheimer's disease (AD). Metabolic remodeling occurs in the central nervous system (CNS) and periphery, even in the early stages of AD. Mitochondrial dysfunction has been widely accepted as a molecular mechanism underlying metabolic disorders. Therefore, focusing on early metabolic changes, especially from the perspective of mitochondria, could be of interest for early AD diagnosis and interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 467 publications
(512 reference statements)
3
79
0
1
Order By: Relevance
“…Although the central nervous system is the most vulnerable area affected by Alzheimer's disease (AD), recent evidence indicates that AD is a multi-organ disorder, which includes metabolic dysfunction and pathological processes in the peripheral organs [30]. Therefore, we were interested in investigating changes in the peripheral organs in two animal models of AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the central nervous system is the most vulnerable area affected by Alzheimer's disease (AD), recent evidence indicates that AD is a multi-organ disorder, which includes metabolic dysfunction and pathological processes in the peripheral organs [30]. Therefore, we were interested in investigating changes in the peripheral organs in two animal models of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many investigators have developed different lipids or nano-conjugated formulations to increase their bioavailability. For example, solid lipid curcumin particles (SLCP) have been shown to prevent neuropathology in AD and other neurodegenerative diseases [25,26,29,30]. More recently, we have been investigating the effects of curcugreen (CGR) on animal models of AD.…”
Section: Introductionmentioning
confidence: 99%
“…MRPL15 is a mitochondrial ribosomal protein necessary for protein synthesis. Mitochondrial dysfunction was found to be an important marker of AD [ 26 , 27 ]. MRPL15 may also be related to the closure or disorder of the biological function of mitochondria and in the function of energy metabolism in schizophrenia [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the central role of mitochondria in AD pathophysiology, a major issue for AD early diagnosis is the identification of new candidate biomarkers related to mitochondrial enzymes and metabolism in peripheral districts such as CSF and blood. Even though the establishment of reliable and consistent mitochondrial biomarkers for AD is still not achieved, studies have been carried out to shed light on the possible use of mitochondrial markers for this purpose [172]. For example, a recent study has demonstrated the possibility of detecting alterations in the expression of nuclear and mitochondrial encoded Oxidative Phosphorylation (OXPHOS) genes in blood samples from AD and MCI patients [173] (Figure 5).…”
Section: Potential Mitochondria Biomarkers For Ad Diagnosismentioning
confidence: 99%